Evaluasi Program Seminar Edukasi Bank Sampah - Rosidin, Egie Rizky Putri; Lestarie, Trie; Dewi, Lusiana; Alviansyah, Muhammad Rafli; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
In an activity, it is necessary to improve by evaluating the management of the program so that there are decisions made for the progress of the program. Program evaluation was carried out on the waste sorting education seminar program and the importance of good waste management in Panglayungan Village, Cipedes District, Tasikmalaya City. The purpose of this study was to determine the program evaluation of the waste bank education seminar activities, measured from the context, input, process and product components. The subject of this research is the management and customers of the PUAN waste bank and the object of research is the waste bank education seminar program. This research uses a qualitative evaluative study approach, with the CIPP (Context, Input, Process, and Product) method. Data were collected using observation techniques, direct interviews in the field and documentation. The results of the study show that the success of the educational seminar program from interviews conducted to the management and management of the waste bank is quite good but there are still shortcomings that must be corrected in socialization to customers. The evaluation of the waste bank program can provide information in the development of future programs and the sustainability of the waste bank education program and improve the performance of the waste bank unit in the future